The importance of studying patterns of composition at professional computer training of the future designers - Akhmetzhanova, G.A.; Bodikov, S.Zh.; Ayazbayeva, S.S. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
This article is devoted to the value of laws of composition at professional computer training of the future designers. One of the principal means of professional formation of project designer is culture in the educational process of the university and the core objective of which is to create specific, conceived artistic effect and consistent with the functional basis of the system by visual subordination components and parts.
Болашақ дизайнерлерді кəсіби-компьютерлік даярлауда композиция заңдылықтарын оқытудың маңызы
Значение изучения закономерностей композиции при профессионально- компьютерной подготовке будущих дизайнеров
Keywords: art; design; culture; composition; feature; profession; painting; technique; modern; stylistic